The impact of academic achievements, organization growth, and leadership development programs on resilient leadership skills among University Students at University Utara Malaysia - Thinesh Rao a/l Chandra Rao,; Noor Hafiza Zakariya,; Sharima Ruwaida Abbas, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In the current landscape of higher education, cultivating resilient leadership in student leaders emerges as a crucial endeavour, propelling students to navigate university complexities. This paper investigates the urgent necessity of comprehending the effects of academic achievements, organisational growth and leadership development programs on resilient leadership skills among university students at University Utara Malaysia. The respondents are 55 undergraduate students from Grantt Student Residential Hall, employing mixed methods incorporating quantitative and qualitative techniques. The research findings show that academic achievements, organisational growth and leadership development programs significantly influence resilient leadership skills. Besides that, they exhibit enhanced adaptability, proficient decision-making skills, and the capacity to motivate and inspire their peers in the face of challenging conditions. This study will contribute substantially to the literature on leadership development in higher education based on the resilient theme. These insights are essential for designing more impactful leadership programs and well-being initiatives among university student leaders. Ultimately, this research empowers upcoming leaders to effectively navigate the complexities of their academic communities and bring about positive transformations. In the dynamic landscape of higher education institutions, fostering resilient leadership skills among students emerges as a catalyst for driving academic achievement, organisational growth, and effective leadership development initiatives.